PENGARUH BAURAN KOMUNIKASI PEMASARAN BERBASIS INSTAGRAM MELALUI BRAND AWARENESS TERHADAP MINAT PEMBELIAN PRODUK DALAM PENYELENGGARAAN SOLO ART MARKET (SAM) - Rahardani, Margareta Ernanda; Sari, Vincentia Indah Puspita (ITB AAS Indonesia Surakarta, 2024)
This research was conducted to examine the influence that occurs between the marketing communication mix, especially advertising as well as public relations and publicity through brand awareness on purchasing interest. Apart from that, this research also reviewed the level of brand awareness that was formed during the implementation of the Solo Art Market (SAM) event. This descriptive quantitative research was conducted on 100 respondents who were SAM visitors who had followed Instagram @soloartmarket.id. The results of this research are that the brand awareness level of SAM visitors is at the purchase stage with a value of 3.96. Advertising does not have an influence through brand awareness on purchasing interest, while public relations and publicity have an influence. This is in line with what was conveyed by respondents through the evaluation form for the implementation of the SAM event.